How agricultural research for development achieves developmental outcomes: learning lessons to inform One CGIAR science and technology policy research - Douthwaite, Boru; Child, K. (International Water Management Institute, 2021)
At the end of 2021, CGIAR Research Programs (CRPs) will be replaced by Initiatives housed within One CGIAR. This new modality is intended to achieve higher levels of impact at a faster rate and at reduced cost compared to the CRPs. As One CGIAR begins, there is a unique opportunity to reflect on what has worked in different contexts. In this paper, we provide findings that relate to One CGIAR’s overarching view of how it will achieve positive and measurable impacts, and for agricultural research for development (AR4D) more generally. Specifically, we draw from three related CRP evaluations to identify how different types of AR4D approaches have contributed to successful outcomes. In the final section of the paper, we present our conclusions and provide a list of recommendations for the science and technology policy of One CGIAR and possibly other integrated research for development programs.